Waste Education Game for 4th Grader of Elementary School - Meti Oktaviani; Erdhi Widiyarto; Abertus Dwiyoga Widiantoro (Journal of Business and Technology, 2021)
Indonesia is the second world largest sea waste producer after China, where waste can make a lot of problems, such as disease and flood, if not taken care properly. Waste is divided by 3 categories: organic waste, inorganic waste, and B3 waste. Learning about waste can be done through playing game. Trash Hero is one of education game that teaches the player, who is 4th grader of elementary school and above, to be able to distinguish the waste categories, how to recycle organic waste to become compost, and also be more aware of sea and land waste. Kids love Trash Hero game, after playing it several times kids become more understand problems about waste and also kids can distinguish waste by its categories.